Adulthood is a gift! : a celebration of "Sarah's Scribbles" - Andersen, Sarah (Sarah C.) (Andersen, Sarah (Sarah C.). Sarah's Scribbles collection, 2024)
With 100 comics, 15 essays, and dozens of photos and sketches, the fifth Sarah's Scribbles book offers a rare look behind the creative process of one of the most original and beloved comic artists of a generation. A comedic companion to her first book, the bestselling Adulthood is a Myth, the artwork and writing in Adulthood is a Gift! is a celebration of the many experiences and life lessons the author has picked up in her decade of making viral, relatable, and award-winning comics and books.